2014
DOI: 10.1097/pcc.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Does Teaching Crisis Resource Management Skills Improve Resuscitation Performance in Pediatric Residents?*

Abstract: A 1-hour crisis resource management teaching session improved time to critical initial steps of pediatric resuscitation and crisis resource management performance as measured by the Ottawa Global Rating Scale. The control group did not develop these crisis resource management skills over 3 months of standard training indicating that obtaining these skills requires specific education. Larger studies of crisis resource education are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…105,106 Specific team training can increase team performance, leadership skills, and task management performance and the effect can last for up to one year. 94,95,100,101,[107][108][109][110][111] On the other hand, leadership training in addition to CPR skills has been shown not to improve actual CPR skills. 112 Assessment instruments (mainly checklists) have been developed, validated, and recommended for individual team members.…”
Section: Training Of Non-technical Skills (Nts) Including Leadership mentioning
confidence: 99%
“…105,106 Specific team training can increase team performance, leadership skills, and task management performance and the effect can last for up to one year. 94,95,100,101,[107][108][109][110][111] On the other hand, leadership training in addition to CPR skills has been shown not to improve actual CPR skills. 112 Assessment instruments (mainly checklists) have been developed, validated, and recommended for individual team members.…”
Section: Training Of Non-technical Skills (Nts) Including Leadership mentioning
confidence: 99%
“…Deliberate practice theories link rehearsal to improvement and expertise 3839 This is well exemplified by the use of rapid cycle deliberate practice training in paediatric resuscitation40 and acute paediatric scenarios in relation to repetition, practice3 and performance 41. It is important to establish ground rules with the learner at the start of the immersion to ensure their safety.…”
Section: What Educational Underpinning Do You Need To Be Aware Of Whementioning
confidence: 99%
“…For the important outcome of skill performance at course conclusion (leader performance), we found low-quality evidence (downgraded for risk of bias and imprecision) from 4 randomized studies 120,126,128,134 and very-low-quality evidence (downgraded for indirectness and imprecision) from 2 observational studies 122,131 that showed that leadership-trained learners demonstrated more frequent leadership behaviors at course conclusion.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…For the important outcome of skill performance at course conclusion (patient tasks) (assessed with time to completion of various patient tasks), we found low-quality evidence (downgraded for risk of bias and imprecision) from 8 randomized trials 110,120,[123][124][125][126][127][128] and very-low-quality evidence (downgraded for risk of bias and indirectness) from 4 observational studies [128][129][130][131] that showed that team or leadership training improved CPR hands-on time and time to initiation of various patient tasks at course conclusion. A dose-response gradient was found.…”
Section: Consensus On Sciencementioning
confidence: 99%